2002
DOI: 10.3748/wjg.v8.i2.363
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of estradiol on hepatocytic oxidative damage

Abstract: Estradiol protects hepatocytes from oxidative damage by means of its antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Concurrently, melatonin administration decreases lipid peroxidation and increases the levels of antioxidants [17]. MDA is a secondary product of oxidative stress formed during lipid peroxidation and is significantly increased by ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, melatonin administration decreases lipid peroxidation and increases the levels of antioxidants [17]. MDA is a secondary product of oxidative stress formed during lipid peroxidation and is significantly increased by ischemia-reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…High-intensity acute exercise causes more oxidative damage than lowintensity exercise (Lovlin et al, 1987), an effect that is especially true when an individual is not accustomed to either the intensity or the duration of the exercise (Viña et al, 2000). The amount of oxidative damage caused by exercise can differ between various tissues and organs (Liu et al, 2002). Exhaustive exercise, such as swimming, affects the level of MDA in the livers of both trained and untrained rats.…”
Section: Discussionmentioning
confidence: 99%
“…This report concluded that the observed gender difference in lipid peroxidation resulted from the suppression of free radical production in females by estradiol. Another study carried out in male rats reported that estradiol protects hepatocytes from oxidative damage due to its antioxidant effects (Liu et al, 2002). Joo et al (2004) reported that the free radicals produced during exercise at times when estradiol levels are high in women can be removed more easily than free radicals produced when estradiol levels are low.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic fibrosis is a common consequence of chornic liver injury from many causes [15][16][17][18][19] , and the sustained hepatic injury is a primary factor for hepatic fibrogenesis [20][21][22][23][24][25][26][27][28] . Preventing hepatocyte from injury is a matter of primary importance in blocking the fibrogenic pathway.…”
Section: Discussionmentioning
confidence: 99%